Exercise preference in stroke survivors: a concept analysis - Dai, Yuting; Shi, Huiling; Ji, Kangling; Han, Yuxin; De Ala, Minerva; Wang, Qing (Frontiers in Neurology, 2024)
Background Exercise preference in stroke survivors is related to their adherence to long-term rehabilitation regimen and functional recovery. Although explored recently, the term exercise preference still lacks a clear definition. Objective The aim of this study is to conceptualize exercise preference in stroke survivors. Methods The Walker and Avant method was applied as a framework for the conceptual analysis of exercise preference. Data from 34 publications were collected using seven databases (PubMed, Web of Science, Embase, CINAHL, CNKI, Wanfang Data, and CBM) and applied in the analysis. The search period was from the inception of the database to April 30, 2023. Results Exercise preference in stroke survivors was defined according to four attributes: priority of choice, behavioral tendency, affective priming, and patience in adherence. The common antecedents of the concept of exercise preference in stroke survivors were classified into patient-related, therapy-related, and environmental-related categories and the consequences were classified into three categories: patient-related, rehabilitation provider–related, and rehabilitation service system–related. Conclusion Exercise preference in stroke survivors refers to the patient’s choice, tendency, affective response, and attitude toward engagement in the recommended rehabilitation regimen. It is beneficial for understanding the essential attributes of exercise preference in stroke survivors by clarifying the concept. In addition, it will facilitate the development of instruments for assessing exercise preference in stroke survivors and the construction of theory-based intervention programs that can improve adherence to exercise rehabilitation.